KORELASI INDEKS MASSA TUBUH DENGAN GLUKOSA DARAH PUASA DAN KOLESTEROL PADA SKRINING KESEHATAN TENAGA KEPENDIDIKAN FAKULTAS KEDOKTERAN UNIVERSITAS ANDALAS - Ramadhani, Jihan; Yulia, Dwi; Fasrini, Ulya Uti; Efrida, Efrida; Khaira, Fathiyyatul (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Introduction. Non-communicable diseases as a cause of death in Indonesia are increasing. Hyperglycemia, hyperlipidemia, and obesity are some of the factors that contribute to an increased risk of non-communicable diseases. Education workers are a group of office workers who are at risk of obesity and non-communicable diseases because they have low physical activity. The study aimed to determine a correlation between body mass index with fasting blood glucose levels and total cholesterol levels in the health screening of educational staff faculty of medicine of Andalas University.  Methods. This research was an analytical study with a cross-sectional design using secondary data for the faculty of medicine of Andalas University health screening that was held on September 08, 2021. The tools used in the study were a calibrated glucometer to measure fasting blood glucose and a calibrated auto-check for total cholesterol examination. 37 data met the inclusion and exclusion criteria. Data were processed and analyzed using univariate and bivariate analysis using the Pearson correlation test.  Results. The result showed that the educational staff of the medical faculty of Andalas University are mostly in the late adult category, most are female and most of them are obese. The mean of body mass index is 25.3 kg/m2, the mean of fasting blood glucose level is 126.57 mg/dL and the mean of total cholesterol level is 205, 14 mg/dL. The bivariate analysis results showed no correlation between body mass index and fasting glucose levels (r = 0.316; p = 0.057) and no correlation between body mass index and total cholesterol levels (r = 0.091; p = 0.591). Conclusions. This study concludes that there is no correlation between body mass index with fasting blood glucose levels and total cholesterol levels in the health screening of educational staff faculty of medicine of Andalas University.